2021
DOI: 10.1186/s10020-020-00222-x
|View full text |Cite
|
Sign up to set email alerts
|

SP1 induced long non-coding RNA AGAP2-AS1 promotes cholangiocarcinoma proliferation via silencing of CDKN1A

Abstract: Background LncRNA can regulate gene at various levels such as apparent genetics, alternative splicing, and regulation of mRNA degradation. However, the molecular mechanism of LncRNA in cholangiocarcinoma is still unclear. This deserves further exploration. Methods We investigated the expression of AGAP2-AS1 in 32 CCA tissues and two CCA cell lines. We found a LncRNA AGAP2-AS1 which induced by SP1 has not been reported in CCA, and Knockdown and over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that many cytoplasmic lncRNAs act as competing endogenous RNAs (ceRNAs) via binding miRNAs ( 24 ). In ICC, several lncRNAs such as lncRNA MT1JP and lncRNA AGAP2-AS1 have been shown to exhibit their tumor-related effects via sponging miRNAs to modulate the expression of various genes involved in tumor progression ( 25 , 26 ). Previously, SNHG12 was also reported to act as a ceRNA in several tumors, such as cervical cancer and oral squamous cell carcinoma ( 19 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that many cytoplasmic lncRNAs act as competing endogenous RNAs (ceRNAs) via binding miRNAs ( 24 ). In ICC, several lncRNAs such as lncRNA MT1JP and lncRNA AGAP2-AS1 have been shown to exhibit their tumor-related effects via sponging miRNAs to modulate the expression of various genes involved in tumor progression ( 25 , 26 ). Previously, SNHG12 was also reported to act as a ceRNA in several tumors, such as cervical cancer and oral squamous cell carcinoma ( 19 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that AGAP2-AS1 modulated the proliferation, migration and invasion of CCA, and Ji et al. confirmed that SP1-induced AGAP2-AS1 promoted CCA proliferation by silencing CDKN1A ( 47 ). Therefore, both GOLGA7B and AGAP2−AS1 regulate CCA progression and are potential therapeutic targets for CCA.…”
Section: Discussionmentioning
confidence: 54%
“…[25][26][27] Our group's previous research has already known that multiple lncRNAs are involved in the regulation of the biological functions of CRC, pancreatic cancer, and cholangiocarcinoma. 12,13,28 In the present study, we screened the differentially expressed lncRNA linc02231 in CRC from the GEO database. as ceRNAs to regulate the expression of miRNAs, leading to the silencing of downstream target genes.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs not only participate in the regulation of various molecular pathways in tumor cells, but also in the modulation of the immune microenvironment, such as immune cell infiltration, extracellular matrix and cancer‐associated fibroblasts 25–27 . Our group's previous research has already known that multiple lncRNAs are involved in the regulation of the biological functions of CRC, pancreatic cancer, and cholangiocarcinoma 12,13,28 …”
Section: Discussionmentioning
confidence: 99%